Current understanding and biotechnological application of the bacterial diterpene synthase CotB2 - Driller, Ronja; Garbe, Daniel; Mehlmer, Norbert; Fuchs, Monika; Raz, Keren; Major, Dan Thomas; Brück, Thomas; Loll, Bernhard (Beilstein Journal of Organic Chemistry, 2019)
CotB2 catalyzes the first committed step in cyclooctatin biosynthesis of the soil bacterium Streptomyces melanosporofaciens. To date, CotB2 represents the best studied bacterial diterpene synthase. Its reaction mechanism has been addressed by isoptope labeling, targeted mutagenesis and theoretical computations in the gas phase, as well as full enzyme molecular dynamic simulations. By X-ray crystallography different snapshots of CotB2 from the open, inactive, to the closed, active conformation have been obtained in great detail, allowing us to draw detailed conclusions regarding the catalytic mechanism at the molecular level. Moreover, numerous alternative geranylgeranyl diphosphate cyclization products obtained by CotB2 mutagenesis have exciting applications for the sustainable production of high value bioactive substances.
Keywords: biotechnology; CotB2; crystal structure; cyclooctatin; diterpene; reaction mechanism; terpene synthase